Peranan Matematika Dalam Perkembangan Teknologi Di Era Digital - Maya Sari Syahrul; Iswan Rina; Nurweni Putri; Islahuddin .; Rosi Ramayanti; Khairannisa Al Azizu (CV. ITTC INDONESIA, 2026)
The rapid advancement of digital technology is inextricably linked to the role of mathematics as a foundational discipline supporting various technological fields. However, some students still perceive mathematics merely as a subject confined to numbers, formulas, and classroom calculations. This community service initiative aims to provide school students with an understanding of the role mathematics plays in technological development within the digital era and to foster their interest in mathematics as a discipline with broad practical applications. The program connects mathematics to digital technology, artificial intelligence, programming, data security, information processing, and other technologies. Implementation methods included presentations, examples of mathematical applications in technology, discussions, and interactive Q&A sessions with participants. The results indicate that students gained a broader understanding of mathematics and recognized that it serves not only as a pure science but also as a foundation and support for the development of various technologies. This initiative is expected to boost students' motivation to study mathematics and encourage them to perceive the interconnections between mathematics, science, and technology in their daily lives.